The Development of Students’ Worksheet Based on RME For the Topic Circle in Junior High School - Ahbi Mahdianing Rum (EduMa: Mathematics education learning and teaching, 2024)
The purpose of this research was to produce a students’ worksheet based on Realistic Mathematics Education for the topic circle in 8th grade at SMPN 01 Kota Bengkulu which was valid and practical. The type of this research was Research & Development using 3 steps of 4D model namely define, design, and develop. The instrument of this research consisted of validity sheets and practically sheets. Vallidity was done by two validators. Practicallity has been tested to 35 students in class VIII.2 at SMPN 1 Kota Bengkulu for the odd semester of academic year 2019/2020. From the research that has been done, it showed the development of students’ worksheet based on Realistic Mathematics Education for the topic circle in 8th included in the category: (1) valid based on 40 items which consisted of 12 material items, 20 contruction items, and 8 language items with the avarage score 4,11 and it was known from: (a) students’ worksheet showed the correctness and suitability according to the sequences of Realistic Mathematics Education syntax on material validation, (b) on the construction validity it showed that the studens’ worksheet was containing good font type and interesting images which made the students’ worksheet easy to read, (c) the sentences were simple, clear, easy to understand, and suit the rule of indonesioan language on languange validation. (2) very practical with the avarage score 4,51 which was known by instruction, steps, images, and the problem in students’ worksheet that were understandable and easy to use by students.